Criminology - Adler, Freda; Laufer, William S.; Mueller, Gerhard O. W. (McGraw-Hill, 2013)
Discusses criminological problems, their origins, and possible solutions in a clear, practical, straightforward fashion. This book intended to incorporate the findings from criminological research into terrorism, while expanding coverage of white-collar and corporate crimes related to the economic downturn